Agroclimatic Regions of Rajasthan - Sen, Amal Kumar (Annals of Arid Zone, 2016)
The paper aims at classifying and mapping agroclimatic regions of Rajasthan. To find out the indices to determine the quantitative relation between agricultural production and climate of Rajasthan three methods dealing with the study of the climatic elements, availability of water at various levels and present cropping pattern respectively were studied and different indices for agroclimatic zonation for Rajasthan were worked out. By faithful correlation of these indices the state has been divided and mapped into five macro and ten micro agro-climatic regions. Each region is homogeneous with its own climatic and agricultural peculiarities.